2019
DOI: 10.1016/j.sleep.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in implementing and assessing outcomes of school start time change in the UK: experience of the Oxford Teensleep study

Abstract: Objective Later school start times for adolescents have been implemented in the US and associated benefits found, although no randomised controlled trials (RCT) have been undertaken. The objective of this study was to evaluate the impact of two school interventions in the UK, a delayed start time and a sleep education programme, on students’ academic performance, sleep outcomes and health-related quality of life. Methods The study had an RCT design to enable an investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…Although these programs are effective and useful in raising subjective awareness, their exclusive application has scarce and low effects on adolescent behavior [136]. As a possible solution, the combined application of sleep hygiene and delayed start times programs [137,138] could represent an effective solution in addressing adolescents' sleep problems by increasing individual motivation and providing a concrete countermeasure to short sleep duration.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Although these programs are effective and useful in raising subjective awareness, their exclusive application has scarce and low effects on adolescent behavior [136]. As a possible solution, the combined application of sleep hygiene and delayed start times programs [137,138] could represent an effective solution in addressing adolescents' sleep problems by increasing individual motivation and providing a concrete countermeasure to short sleep duration.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In recognition of the insufficient sleep experienced by adolescents and the importance of sleep for functioning and health, school-based initiatives at the organizational and classroom level need implementing. Our Teensleep research group has developed and evaluated such an initiative in an effort to improve adolescent sleep in the UK [71,72]. This work follows in the footsteps of sleep education interventions introduced worldwide: for example, in the USA [73], Australia [74,75] and Asia [76].…”
Section: School-based Interventionsmentioning
confidence: 99%
“…The CASQ had been widely used in the area of sleep medicine, children's health care, nursing research, and psychology and education. [35][36][37][38] The purpose of this work was to translate, adapt, and evaluate the psychometric properties of a Chinese version of the CASQ (C-CASQ) [see Additional File 1] using a sample of adolescents from Taiwan. We found that the C-CASQ had good psychometric properties and was consistent in measuring sleepiness differences in morning and evening chronotypes.…”
Section: Discussionmentioning
confidence: 99%